Nonlinear stability analysis of motor bogies for high-speed trains. (October 2019) - Xu, Kun; Zeng, Jing; Huang, Cai-Hong
The traction motor flexibly suspended on the bogie frame is conducive to the lateral dynamic performance of high-speed trains. At present, most of the researches about the influences of suspension parameters of the traction motor on the stability of the bogie are limited to the linear system. In this paper, according to the suspension mode of the traction motor of a certain type of high-speed train in China, the dynamic equations of the motorized bogie with eight degrees of freedom are derived, and the nonlinear stability of the bogie system is analyzed. The bifurcation diagrams of the bogie system with different motor suspension parameters are obtained by using the continuation algorithm, and the linear and nonlinear critical speeds of the system are studied. The study shows that the suspension stiffness, damping coefficient, and the mass of the motor significantly affect the critical speeds of the bogie system. Then the mechanisms of the influence of suspension parameters on the linear and nonlinear critical speeds of the bogie are analyzed by the root locus method and Hopf bifurcation normal form theory, respectively.